THE ADVERSE EFFECTS OF CULTURAL DIFFERENCES AND LEADERSHIP OF CULTURALLY DIVERSE WORK TEAMS DEVELOPMENT OF INTERCULTURAL COMPETENCE IN MULTINATIONAL COMPANIES IN THE NETHERLANDS - Ekow Asampong, Alex (Digital Repository of Theses - SSBM Geneva, 2021)
I thank God for giving me life, strength, knowledge and wisdom to finish this research successfully despite the severe health challenges I encountered during the study. My heartfelt gratitude also goes to Dr Mario Silic, my supervisor at the Swiss School of Business and Management, Switzerland, for guiding and providing me with valuable comments to complete this research successfully. Your dedication, professional experience, excellent communication skills and your passion have contributed to this study tremendously, and I will forever remain grateful to you. Furthermore, my appreciation goes to all other supervisors who contributed initially to this research. This research has also become successful due to the kind support and the beautiful encouragements of Eugenia Tetteh, Ephraimina Tetteh and Daniel Alexander Asampong. Anytime I became tired and weary, you gave me the hope to keep moving on, and I will remain grateful to you. My special gratitude also goes to Dr M.S. van Sandwijk, an Internist at the UMC, Amsterdam and Dr H. Westerborg, my General Practitioner in Amsterdam for their high level of professionalism and great medical care in the course of my studies. My special appreciation goes to Marlies Schuman, one of the directors at the Institute of International Business School of Utrecht University of Applied Sciences, the Netherlands, for your thoughtful support and encouragement. I will also remain grateful to all the colleagues at the Institute of International Business Studies Utrecht, the Netherlands, for your moral support. Finally, I thank all team leaders and members in multinational companies in the Netherlands who participated with their rich knowledge and experience for this research and also not forgetting friends who in various ways, assisted me.